The influence of the map-assisted problem-based learning model and cognitive style on the spatial and critical thinking abilities of junior high school students - Hidayati, Armawati; Rusijono, Rusijono; Arianto, Fajar; Prasetya, Sukma Perdana; Murtini, Sri (Edelweiss Applied Science and Technology, 2025)
This study investigates the influence of the map-assisted Problem-Based Learning (PBL) model and cognitive styles on the spatial and critical thinking abilities of junior high school students. A quasi-experimental design with a 2×2 factorial structure was employed, involving 122 eighth-grade students. Participants were divided into two groups based on the learning model (map-assisted PBL and conventional PBL) and two cognitive style categories (Field Independent and Field Dependent). Data collection involved pre- and post-tests assessing spatial and critical thinking skills. The results of Multivariate Analysis of Variance (MANOVA) indicated that the map-assisted PBL model significantly enhanced both spatial and critical thinking abilities. Cognitive style also had a notable impact on spatial skills, with Field Independent students outperforming their Field Dependent counterparts. Additionally, a significant interaction between the learning model and cognitive style was observed concerning spatial abilities, although no significant effect was found for critical thinking. These findings underscore the importance of integrating cognitive characteristics into instructional design and highlight the effectiveness of map-assisted PBL in fostering spatial and critical thinking skills within social studies education. Practical implications suggest that educators should tailor learning strategies to students’ cognitive styles to improve learning outcomes.